2019
DOI: 10.5604/01.3001.0013.6006
|View full text |Cite
|
Sign up to set email alerts
|

Polish Agri-Food Trade With Non-Eu Countries – A Gravity Model Analysis

Abstract: The main aim of the article was to indicate the influence of selected determinants of Poland’s agri-food export to countries outside the European Union. Although European Union countries have been the Poland’s main trading partners for years, the share of third countries in total Polish trade has gradually been increasing. In the case of Polish agri-food trade, a different tendency is observed, as the importance of non-EU countries is decreasing. In the analysis, covering the years 2000-2016, the gravity model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For the period 2000 to 2016, Sapa and Droždz (2019) investigated the determinants of Poland’s agri-food exports to non-EU countries. According to the research GDP and agricultural value-added promote trade between Poland and non-EU countries.…”
Section: Review Of Related Empirical Literaturementioning
confidence: 99%
“…For the period 2000 to 2016, Sapa and Droždz (2019) investigated the determinants of Poland’s agri-food exports to non-EU countries. According to the research GDP and agricultural value-added promote trade between Poland and non-EU countries.…”
Section: Review Of Related Empirical Literaturementioning
confidence: 99%
“…Many variables have been added to the research models. (Sapa & Droždz, 2019) argued that the addition of variables improves the basic methodology of the selected gravity equation. In the other hands, according to (Sherphed, 2019) "Traditionally, gravity models have been based largely on intuitive ideas as to which variables are likely to influence trade", without focusing on the structure of the model.…”
Section: Discuss the Application Of Gravity Models In Studies Of Trade Flowsmentioning
confidence: 99%
“…Later, Sokvibol Kea et al (2019) also added the variable of the total import value of rice to the importing country to represent the size of the demand for rice of the importing country when analyzing the main determinants of Cambodia's rice export performance in the international market. Morevoer, Sapa and Droždz (2019) added the agriculture value-added variable of the exporting country and demonstrated that it has a good meaning in the model. This in fact has also shown a certain inequality.…”
Section: Discuss the Application Of Gravity Models In Studies Of Trade Flowsmentioning
confidence: 99%